2013
DOI: 10.1021/la402621r
|View full text |Cite
|
Sign up to set email alerts
|

Defined DNA-Mediated Assemblies of Gene-Expressing Giant Unilamellar Vesicles

Abstract: The technological aspects of artificial vesicles as prominent cell mimics are evolving toward higher-order assemblies of functional vesicles with tissuelike architectures. Here, we demonstrate the spatially controlled DNA-directed bottom-up synthesis of complex microassemblies and macroassemblies of giant unilamellar vesicles functionalized with a basic cellular machinery to express green fluorescent protein and specified neighbor-to-neighbor interactions. We show both that the local and programmable DNA pairi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 59 publications
(105 reference statements)
0
36
0
Order By: Relevance
“…For example, it has been reported that lipid compartments can form clusters following simple adhesive forces [28,14]. Protein synthesis is still possible in such assemblies [27], and the idea of prototissue has been put forward, as supported by some pioneer work on membrane-to-membrane connective mojeties [49,42].…”
Section: Semi-synthetic Minimal Cells (Ssmcs)mentioning
confidence: 99%
“…For example, it has been reported that lipid compartments can form clusters following simple adhesive forces [28,14]. Protein synthesis is still possible in such assemblies [27], and the idea of prototissue has been put forward, as supported by some pioneer work on membrane-to-membrane connective mojeties [49,42].…”
Section: Semi-synthetic Minimal Cells (Ssmcs)mentioning
confidence: 99%
“…1 the spatially controlled DNA-directed bottom-up synthesis of complex tissue-like assemblies composed of artificial vesicles was implemented. In addition to the specified neighbor-to-neighbor interactions DNA also provided the genetic blueprint for the synthesis of functional proteins [30] (Fig. 2).…”
Section: Programmable Nano-bioreactors For Synthetic Biologymentioning
confidence: 99%
“…Scale bars: 1000 µm (b, e, h, l), 50 µm (c, f, j, m). Fluorescence micrographs b, c, e, f modified from Hadorn et al [30]; h, j, l, m modified from Hadorn et al [31].…”
Section: Formal Framework For Compartmentalized Reactionsmentioning
confidence: 99%
See 2 more Smart Citations